2016
DOI: 10.1002/adma.201603356
|View full text |Cite
|
Sign up to set email alerts
|

Functional Gradient Inverse Opal Carbon Monoliths with Directional and Multinary Porosity

Abstract: Nanoporous monoliths with hierarchical nanostructure are prepared via in situ assembly of template and carbon precursor gel by controlled ultracentrifugation experiments. Benefits of the gradient porosity are demonstrated for the Li-O battery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…The centrifugation with the direction of centrifugal force along the height of microholes was then applied to the CaCO 3 NPs/PDMS‐composite‐filled PU template by the using of swing‐bucket centrifuge rotor. [ 32 ]…”
Section: Resultsmentioning
confidence: 99%
“…The centrifugation with the direction of centrifugal force along the height of microholes was then applied to the CaCO 3 NPs/PDMS‐composite‐filled PU template by the using of swing‐bucket centrifuge rotor. [ 32 ]…”
Section: Resultsmentioning
confidence: 99%
“…A centrifugation approach was used to build crack‐free gradient porous carbon materials. Polystyrene spheres with three different sizes were used as templates with a resorcinol‐formaldehyde sol . Materials with bimodal and trimodal porosity (Figure ) were produced.…”
Section: Production Of Gradient Materialsmentioning
confidence: 99%
“…Ac entrifugation approachw as used to build crack-free gradientp orousc arbon materials.P olystyrene spheres with three different sizes were used as templates with ar esorcinol-formaldehyde sol. [46] Materials with bimodal and trimodal porosity ( Figure 5) were produced.A reas with different porosity can be clearly seen in the scanninge lectron microscopy micrographs.I tw as shown that the performance of a Li-O 2 cell is heavilyi nfluenced by the porous structure.…”
Section: Production Of Gradient Materialsmentioning
confidence: 99%
“…At lower rotational speeds, sedimentation and diffusion are in equilibrium and exponential concentration gradients are generated (sedimentation equilibrium experiments). The behavior of nanoparticles in the AUC is well‐known …”
mentioning
confidence: 99%